2010
DOI: 10.1074/jbc.m110.103010
|View full text |Cite
|
Sign up to set email alerts
|

cPLA2 Regulates the Expression of Type I Interferons and Intracellular Immunity to Chlamydia trachomatis

Abstract: Infection with the obligate bacterial intracellular pathogenChlamydia trachomatis leads to the sustained activation of the small GTPase RAS and many of its downstream signaling components. In particular, the mitogen-activated protein kinase ERK and the calcium-dependent phospholipase cPLA 2 are activated and are important for the onset of inflammatory responses. In this study we tested if activation of ERK and cPLA 2 occurred as a result of RAS signaling during infection and determined the relative contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 72 publications
3
38
1
2
Order By: Relevance
“…The recent report identifying a C. trachomatis gene as a lyso-PC acyltransferase that functions with a host acyl-CoA-binding protein to remodel PC following C. trachomatis infection (22) is also incompatible with the analytical data. The selective degradation of polyunsaturated PE molecular species and the release of arachidonic acid into the medium are consistent with the activation of cPLA 2 observed by others (21,53,62). However, cPLA 2 activation appears to be related to the cellular immunity response to chlamydial infection rather than participating in bacterial phospholipid synthesis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The recent report identifying a C. trachomatis gene as a lyso-PC acyltransferase that functions with a host acyl-CoA-binding protein to remodel PC following C. trachomatis infection (22) is also incompatible with the analytical data. The selective degradation of polyunsaturated PE molecular species and the release of arachidonic acid into the medium are consistent with the activation of cPLA 2 observed by others (21,53,62). However, cPLA 2 activation appears to be related to the cellular immunity response to chlamydial infection rather than participating in bacterial phospholipid synthesis.…”
Section: Discussionsupporting
confidence: 71%
“…The data showed that the new PE, PG, and CL have molecular species profiles consistent with the bioinformatic model that predicts they arise from the same PA pool. 2 , and the degraded phospholipids may be subsequently modified by putative C. trachomatis acyltransferases to create new molecular species (21,53). The reduction in host PE molecular species containing polyunsaturated fatty acids in C. trachomatis-infected cultures was consistent with the degradation and/or remodeling of selected PE molecular species.…”
Section: Phospholipid Content and Synthesis In Ctr-infected Helamentioning
confidence: 70%
“…This work was also supported by the American Lebanese Syrian Associated Charities. The atomic coordinates and structure factors (code 4Q9N) cells found that a decrease in cPLA 2 activity has no effect on C. trachomatis growth (5). In mouse cells, cPLA 2 knockdown increases chlamydial titers, suggesting that cPLA 2 is more likely involved in intracellular immunity (5).…”
mentioning
confidence: 99%
“…The atomic coordinates and structure factors (code 4Q9N) cells found that a decrease in cPLA 2 activity has no effect on C. trachomatis growth (5). In mouse cells, cPLA 2 knockdown increases chlamydial titers, suggesting that cPLA 2 is more likely involved in intracellular immunity (5). One function of FASII is to generate the 3-hydroxy fatty acids for lipopolysaccharide synthesis in Gram-negative bacteria (6).…”
mentioning
confidence: 99%
“…Previous work from our laboratory and others has demonstrated that the IRGM (GMS) proteins play a particularly important role in innate immune resistance to intracellular bacteria and protozoa in mice (8, 14, 16 -26). Absence of Irgm1, for instance, leads to a striking susceptibility to multiple organisms, including Toxoplasma gondii (8,19), Salmonella typhimurium (25), Listeria monocytogenes (19), Chlamydia trachomatis (27,28), and Mycobacterium species (20, 21). In comparison, absence of the GKS proteins Irgd or Irga6 results in relatively weak phenotypes (8,13,19).…”
mentioning
confidence: 99%